Do exogenous ketones improve intermittent running performance in division II female soccer players? - Pederson, J. J. (2025)
The study investigated the efficacy of exogenous ketones in Division II collegiate female soccer athletes during a 20m shuttle run. Thirteen female Division II soccer players (Age: 20 ± 2 yrs, HT: 161 ± 13 cm, WT: 64.2 ± 12.6 kg, BF%: 22.6 ± 7.3 %, Last Known Period: 18.5 ± 20.5 days) completed three YOYO intermittent recovery test level 1 runs (YOYO) in a double-blinded, randomized crossover design. Each trial was separated by four days for recovery. The initial trial served as the baseline, and participants were then randomly assigned to either a placebo or exogenous ketone condition for trials two and three. A GLM repeated measures ANOVA revealed no significant effect on YOYO distance (meters) (F = 2.060, p = 0.149) from consuming exogenous ketones compared to baseline or a placebo. A GLM repeated measures ANOVA found a significant effect of time on blood ketone levels following a supplement and test protocol (F = 22.252, p < 0.001, partial n² = 0.650). Ketone levels increased significantly from 0.731 mmol/L (SD = 0.2594) at 30 minutes post-supplement consumption to 1.0 mmol/L (SD = 0.3266) at 8 minutes post-test (p = .014) and continued to rise to 1.177 mmol/L (SD = 0.3876) at 20 minutes post-test. A GLM repeated measures ANOVA showed no significant effect of exogenous ketones on post-test blood lactate levels (F = 1.408, p = 0.264, partial n² = 0.105). Pairwise comparisons with a Bonferroni adjustment confirmed no significant differences: baseline (M = 7.77 mmol/L, SD = 1.76) vs. placebo (M = 8.85 mmol/L, SD = 2.62), p = 0.722; baseline vs. ketone (M = 7.78 mmol/L, SD = 1.76), p = 1.0; and placebo vs. ketone, p = 0.731. There were no significant differences across conditions for VO2max as calculated from YOYO performance (F = 1.870, p = 0.176, np2 = 0.135). Regression analysis indicated that blood ketone levels did not significantly predict YOYO performance (R-square = 0.154, p = 0.663). However, though not statistically significant, a 667.86m increase per 1 mmol/L suggests a potentially meaningful practical effect. Regression analysis indicated that BF% was a significant predictor of YOYO performance (p = 0.001, CI 95%). For each 1% increase in BF%, the YOYO distance decreased by 44.41m (p = 0.033).